(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Fatal road traffic accidents are the major cause of concern all over the world. Expansion in road network, motorization and urbanization in the country has been accompanied by a rise in road accidents leading to fatal road traffic injuries. Deaths due to road traffic accident continue to be one of the leading causes of mortality and morbidity in India; Apart from death, disabilities and hospitalization with severe socio-economic costs are also major problems. The present study aims to find out the various pattern of injuries from fatal road traffic accidents and the various factors influencing these incidents. For this purpose a prospective study of 2 years was carried out on the victims of road traffic accidents brought for medico-legal autopsy. Out of total 559 cases, highest incidence was seen between the age group of 21-30 years comprising 126 (22.50%) cases, compared to females, male comprised a majority and constituted 481 (86.05%) cases. Motorcycles were most frequently used vehicles, particularly in rural population, because of its affordable costs. Maximum numbers of injuries were present in the vulnerable parts like head and extremities. Road traffic accidents constitute a major public health problem in our setting and this study emphasizes the importance of road safety awareness and traffic rules.